A novel algorithm for TOP-K optimal path on complex multiple attribute graph. (5th May 2020) - Zhang, Kehong; Li, Keqiu
In the rapidly-changing information world, the various users and personalised requirements lead to an urgent need for complex multiple attribute decision-making. In addition, the TOP-K path of single attribute decision cannot meet the actual needs. The TOP-K mainly has non-repeatable vertex, repeatable vertex, index and other algorithms. But these techniques are mainly based on the single attribute. There are few documents introducing the complex multiple attribute decision-making problem so for. Therefore, a Tdp algorithm is presented in this paper. Firstly, it uses the technology of interval number and extreme value to solve the uncertain attribute value. Then, TOPSIS technique solves the complex multiple attribute decision-making problems. By this way, the comprehensive score is achieved. Secondly, the paper proposes blocking and bidirectional shortest path algorithm for TOP-K optimal path. Finally, comparison and analysis between Tdp and the Yen were made. Result confirms that Tdp algorithm improves the TOP-K optimal technology.